CBMS-1 Targeting amino acid metabolic vulnerabilities in IDH-mutant and IDH-wildtype gliomas. (6th December 2021) - Ohba, Shigeo; Hirayama, Akiyoshi; Hitachi, Keisuke; Yamaguchi, Hisateru; Teranishi, Takao; Mukherjee, Joydeep; Pieper, Russell; Hirose, Yuichi
Abstract: IDH-wildtype glioma and IDH-mutant glioma have different genetical and metabolic background although their histological appearances are similar. To reveal the difference in metabolites between IDH-wildtype and IDH-mutant glioma, and to find the effective treatment targeting cancer metabolism according to the status of IDH in gliomas, two artificial cell lines made from normal human astrocyte, NHAE6E7hTERTRas (IDH-wildtype) and NHAE6E7hTERTIDHmut (IDH-mutant), were investigated. RNA-seq analysis revealed that about 10% of changed genes were involved with metabolism. Capillary electrophoresis- and ion chromatography-coupled mass spectrometry revealed that the amount of asparagine was lower in NHAE6E7hTERTRas cells compared with NHAE6E7hTERTIDHmut cells. L-asparaginase, which converts asparagine into aspartate, was more effective in former cells. L-asparaginase induced autophagy and inhibition of autophagy by 3-MA suppressed L-asparaginase-induced antitumor effect. Adding asparagine into the culture medium rescued the antitumor effect of L-asparaginase. L-asparaginase increased the expression of asparagine synthetase (ASNS) and inhibition of ASNS enhanced the antitumor effect of L-asparaginase. Metabolic assay also showed the lower amount of glutamine, glutamate and 2-oxoglutarate in NHAE6E7hTERTIDHmut cells than NHAE6E7hTERTRas cells. Inhibition of GLUD1 which converts glutamate to 2-oxoglutarate, suppressed proliferation of the cells by inducing ROS and apoptosis in NHAE6E7hTERTIDHmut cells. Exogeneous dimethyl 2-oxoglutarate rescued the cytotoxicity by GLUD1 inhibitor, suggesting decreased 2-oxoglutarate was associated with GLUD1 inhibitor-induced cytotoxicity. ROS inhibitor, NAC suppressed GLUD1 inhibitor-induced ROS, apoptosis, and cytotoxicity in NHAE6E7hTERTIDHmut cells, revealing that cytotoxicity by GLUD1 inhibitor was at least partially due to the inhibitor-induced ROS. Other IDH-wildtype glioma cells, U251 and U87 showed similar sensitivity to L-asparaginase and GLUD1 inhibitor to NHAE6E7hTERTRas, whereas U251 expressing mutant IDH1 showed similar sensitivity to GLUD1 inhibitor to NHAE6E7hTERTIDHmut, which suggested that the difference of sensitivity to each reagent was due to the status of mutant IDH. L-asparaginase and GLUD1 inhibitor will be new therapeutic options for IDH-wildtype glioma and IDH-mutant glioma, respectively.